The DQQ is a valid tool to collect population-level food group consumption data: A study among women in Ethiopia, Vietnam, and Solomon Islands - Uyar, Betül T.M.; Talsma, Elise F.; Herforth, Anna W.; Trijsburg, Laura E.; Vogliano, Chris; Pastori, Giulia; Bekele, Tesfaye Hailu; Huong, Le Thi; Brouwer, Inge D. (Elsevier, 2023)
Background The Diet Quality Questionnaire (DQQ) is a rapid dietary assessment tool designed to enable feasible measuring and monitoring of diet quality at population level in the general public.